Engineering Dissipative Channels for Realizing Schrödinger Cats in SQUIDs - Everitt, Mark J.; Spiller, Timothy P.; Milburn, Gerard J.; Wilson, Richard D.; Zagoskin, Alexandre M. (Frontiers in ICT, 2014)
We show that by engineering the interaction with the environment there exists a large class of systems that can evolve irreversibly to a cat state. To be precise we show that it is possible to engineer an irreversible process so that the steady state is close to a pure Schrödinger’s cat state by using double well systems and an environment comprising two-photon (or phonon) absorbers. We also show that it should be possible to prolong the lifetime of a Schrödinger’s cat state exposed to the destructive effects of a conventional single-photon decohering environment. In addition to our general analysis we present a concrete circuit realisation of both system and environment that should be fabricatable with current technologies. Our protocol should make it easier to prepare and maintain Schrödinger cat states which would be useful in applications of quantum metrology and information processing as well as being of interest to those probing the quantum to classical transition.